Self–other agreement in personality traits and profiles across cultures: A multirater, multiscale study in Blacks and Whites in South Africa. Issue 6 (24th January 2018) - Fetvadjiev, Velichko H.; Meiring, Deon; van de Vijver, Fons J. R.; Nel, J. Alewyn; De Kock, François
Abstract: Objective: Despite the importance of self–other agreement for the validity of trait models, few studies have assessed cultural differences systematically. We examined self–other agreement in traits and profiles in the more collectivistic Black group and the more individualistic White group in South Africa. Method: Participants were 172 Black and 198 White students, and one relative and one friend of each student. Participants completed a behavior‐based and a trait‐adjective‐based inventory. Results: Aggregated across traits and raters, there were no cultural differences in trait agreement. However, agreement was stronger for social‐relational concepts in Blacks and for personal growth concepts in Whites, providing moderate support for the hypothesis of stronger agreement on culturally more salient traits. Trait agreement was stronger in Blacks' relatives and Whites' friends, but there was no such interaction in profile agreement. The differences in profile agreement (higher in Whites than in Blacks) involved normative agreement and were mediated by dialecticism (higher in Blacks) and social desirability (higher in Whites). Results with the two inventories were similar. Conclusions: In the framework of trait consistency research, cultural differences in self–other agreement may be limited compared to differences in perceived trait consistency, although sizable compared to differences in actual behavior consistency.